A new non‐isolated free ripple input current bidirectional DC‐DC converter with capability of zero voltage switching. (26th December 2017) - Saadatizadeh, Zahra; Chavoshipour Heris, Pedram; Sabahi, Mehran; Tarafdar Hagh, Mehrdad; Maalandish, Mohammad
Summary: In this paper, a new nonisolated free ripple input current bidirectional dc‐dc converter with capability of zero voltage switching (ZVS) is proposed. The free ripple input current condition at low voltage side is achieved by using third winding of a coupled inductor and a capacitor for the whole range of duty cycles. In the proposed structure, the voltage conversion ratio can be more increased by adding the turn ratio of the second winding of the coupled inductor for the whole range of duty cycles. By adjusting the value of an auxiliary inductor in the topology of the converter, according to the power, the ZVS operation of the implemented 2 switches can be achieved throughout the whole power range. The mentioned features of proposed converter are validated theoretically for both boost and buck operations. In this paper, the proposed converter is analyzed for all operating modes. Moreover, all equations of the voltages and currents of all components, voltage conversion ratio, the required conditions for ZVS operation of switches, and also required conditions for canceling input current ripple at low voltage side are obtained. Finally, the performance of the proposed converter is reconfirmed through experimental and EMTDC/PSCAD simulation results. Abstract : In this paper, a new nonisolated free ripple input current bidirectional dc‐dc converter with capability of zero voltage switching (ZVS) is proposed. In the proposed converter by using a 3‐winding coupled inductor, the voltage conversion ratio is increased and the free ripple input current condition at low voltage side is achieved for a whole range of duty cycles in comparison with common topologies. The proposed converter uses an auxiliary inductor for achieving ZVS turning ON for 2 switches for different values of output power.